Pre-Service Teachers’ Perception and Vision about TPACK and Its Implementation - Arrizalu Arsa Ringotama (Celt: A Journal of Culture, English Language Teaching & Literature, 2020)
The need for educators to integrate the use of technology in the classroom is growing for the past few years. However, previous studies indicated that the use of Information and Communications Technology (ICT) is still at a low level of what the education program requires. Furthermore, it seems that in the field of language education, there is limited research focusing on pre service teachers (PTs). Therefore, to address this gap, this paper aims at investigating how the pre service teacher's understanding of the TPACK principle and how they will apply TPACK in their classroom. This mix-method study is using TPACK questionnaire and interview through a random sampling of 68 pre-service teachers of English Education Department of UNS. Furthermore, the results revealed that most of the participants understood the concept of TPACK well, and they also had various ways to apply it in their classroom. It is expected that knowing pre service teachers' (PTs) perceptions about TPACK in teaching and learning process that can be beneficial for both English Education Department programs and PTs, such as understanding the PTs' teaching abilities, development of the use of technology in teaching by pre service teachers in order to improve teacher department programs itself to develop the teaching practice with the support of technology. In addition, this study has implications for experts interested in the development and assessment of pre service teachers' understanding of teaching with technology.